The Role of Artificial Intelligence (AI) in the Transformation of Human Resource Analytics on the Performance of Generation Z Employees in Digital Startup Companies in Indonesia - Ismandra Ismandra; Supriadi Supriadi (Fundamental and Applied Management Journal, 2026)
This study examines the role of Artificial Intelligence (AI) in transforming human resource analytics and its impact on the performance of Generation Z employees in digital startup companies in Indonesia. The topic is relevant due to the rapid growth of startups and the increasing use of AI in human resource management. Generation Z, as a dominant workforce, is known for being digitally oriented, adaptable, and comfortable with data-driven environments, making it important to understand how AI-based analytics influence their performance. This research aims to analyze how AI tools improve decision-making, employee engagement, productivity, and performance evaluation. The study uses a quantitative approach with a survey involving Generation Z employees in digital startups. Data were analyzed using statistical methods to examine the relationship between AI-based HR analytics and employee performance. The results show that AI improves efficiency in recruitment, performance monitoring, and employee development, which positively affects productivity and job satisfaction. In addition, AI helps organizations make more accurate and strategic decisions. In conclusion, the use of AI in HR analytics plays an important role in improving employee performance and provides a competitive advantage for digital startups in Indonesia.